1
$\begingroup$

I am trying to calculate the square amplitude for Bhabha scattering $e^-(p_1)e^+(p_2)\rightarrow e^-(p_3)e^+(p_4)$ using the spinor-helicity formalism but one of the interference terms just will not fit.

The unpolarised, spin-averaged squared amplitude should be $$\overline{|M|^2}=2e^4\left(\frac{u^2+t^2}{s^2}+\frac{u^2+s^2}{t^2}+\frac{2u^2}{st}\right).$$

The first term comes from the s-channel, the second from the t-channel and the last term is an interference term and there is also where my problem originates.

The matrix elements for the s- and t-channel are $$M_s=\frac{-ie^2}{s}\overline{v}_2\gamma^\mu u_1\times\overline{u}_3\gamma_\mu v_4,\quad M_t=\frac{-ie^2}{s}\overline{v}_2\gamma^\mu v_4\times\overline{u}_3\gamma_\mu u_1.$$

We have four possible helicity combinations for each of the channels, which reduce down to two due to crossing symmetry. The four remaining are the following. $$M^{-++-}_s=(M^{+--+}_s)^\ast=\frac{-ie^2}{s}\langle2\gamma^\mu1]\langle3\gamma_\mu4]=\frac{2ie^2}{s}\langle23\rangle[14],$$ $$M^{-+-+}_s=(M^{+-+-}_s)^\ast=\frac{-ie^2}{s}\langle2\gamma^\mu1]\langle4\gamma_\mu3]=\frac{2ie^2}{s}\langle24\rangle[13],$$ $$M^{-++-}_t=(M^{+--+}_t)^\ast=\frac{-ie^2}{t}\langle2\gamma^\mu4]\langle3\gamma_\mu1]=\frac{2ie^2}{t}\langle23\rangle[41],$$ $$M^{--++}_t=(M^{++--}_t)^\ast=\frac{-ie^2}{t}\langle4\gamma^\mu2]\langle3\gamma_\mu1]=\frac{2ie^2}{t}\langle43\rangle[21],$$

Only the same helicity configurations can interfere. Thus, I find that $$|M^{-+-+}_s|^2=|M^{+-+-}_s|^2=4e^4\frac{t^2}{s^2},$$ $$|M^{--++}_t|^2=|M^{++--}_t|^2=4e^4\frac{s^2}{t^2},$$ $$|M^{-++-}_s+M^{-++-}_t|^2=4e^4\frac{u^2}{s^2}+4e^4\frac{u^2}{t^2}+\frac{e^4}{st}\Big(\underbrace{\langle23\rangle[23][14]\langle41\rangle+\langle32\rangle[32][14]\langle41\rangle}_{=-2u^2}\Big).$$

Hence, summing over all helicity configurations (gives a factor of 2) and spin-averaging by dividing by 4, I arrive at the following result: $$\overline{|M|^2}=2e^4\left(\frac{u^2+t^2}{s^2}+\frac{u^2+s^2}{t^2}-\frac{2u^2}{st}\right),$$ which obviously has the wrong sign in front of the last term.

I do not know where I have made a mistake in my calculation. Here is the bit that leads to the third term: $$M^{-+-+}_s\times(M^{-+-+}_t)^\ast\sim\langle23\rangle[14]\underbrace{\Big(\langle23\rangle[41]\Big)^\ast}_{=[32]\langle14\rangle},$$ $$M^{-+-+}_t\times(M^{-+-+}_t)^\ast\sim\langle23\rangle[41]\underbrace{\Big(\langle23\rangle[14]\Big)^\ast}_{=[32]\langle41\rangle}.$$

As we see, we have a factor $[14]\langle14\rangle=-[14]\langle41\rangle=-2p_1p_4=-u^2$ in the first line and equally in the second since $[14]\langle14\rangle=[41]\langle41\rangle$.

Does anybody have an idea what I did wrong?

$\endgroup$
1
$\begingroup$

It turns out that this is a case of 'know your Feynman rules'. First of all, the helicity notation in my post is not consistent. We should have the following matrix elements: $$M^{----}_s=\frac{-ie^2}{s}\langle2\gamma^\mu1]\langle3\gamma^\mu4]=\frac{2ie^2}{s}\langle23\rangle[14],$$ $$M^{--++}_s=\frac{-ie^2}{s}\langle2\gamma^\mu1][3\gamma^\mu4\rangle=\frac{2ie^2}{s}\langle24\rangle[13],$$ $$M^{----}_t=\frac{-ie^2}{t}\langle3\gamma^\mu1]\langle2\gamma^\mu4]=\frac{2ie^2}{s}\langle32\rangle[14],$$ $$M^{-+-+}_t=\frac{-ie^2}{t}\langle3\gamma^\mu1][2\gamma^\mu4\rangle=\frac{2ie^2}{s}\langle34\rangle[12].$$

Now it is clear that $M^{----}_{s,t}$ interfere. However, what I did not consider is that there is a relative sign between both diagrams due to the fact that the t-channel diagram is related to the s-channel diagram by switching the positron with the electron. This incurs a minus sign. We find that $$|M^{----}_{s-t}|^2=\underbrace{|M^{----}_s|^2}_{=4e^4u^2/s^2}+\underbrace{|M^{----}_t|^2}_{=4e^4u^2/t^2}-\frac{4e^4}{st}\Big(\underbrace{\langle23\rangle[23]\langle41\rangle[14]+[32]\langle32\rangle[41]\langle14\rangle}_{=-2u^2}\Big)$$ $$=4e^4\left(\frac{u^2}{s^2}+\frac{u^2}{t^2}+\frac{2u^2}{st}\right),$$ which together with $|M^{--++}_s|^2$ and $|M^{-+-+}_t|^2$ gives the right result.

$\endgroup$
1
  • $\begingroup$ Hey, quick clarification. By $M(----)$ do you mean $M(e^-_L e^+_R\to e^-_L e^+_R)$? So the 'signs' in your amplitude $M(----)$ are the helicities of the SPINORS involved(eg right handed positron $e^+_R$ has a left helicity spinor), and not the particle/antiparticles? $\endgroup$
    – GRrocks
    Jul 8 at 23:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.